Evaluation Du Traitement Chirurgical Des Fractures De Type Burst Non Deficitaire - Kpelao, Essossinam; Meyer, Mikael; Martins, Vivien Mendes; Chirossel, Jean-Paul; Darre, Tchin; Gay, Emmanuel (European Scientific Journal, ESJ, 2016)
Introduction: The difficulty in treating of burst fracture is marked by secondary kyphosis. We expose our results in this challenge. Material and Methods: We retrospectively evaluated on preoperative, postoperative, and follow up scanners of 40 patients operated between 2007 and 2012 in the neurosurgery department of the CHU Grenoble these parameters: vertebral kyphosis (CV), regional kyphosis (CR), traumatic regional angulation (ART) and the inter-pedicular distance. The follow-up should be at least a year. Results: The mean age of patients was 39.2 years. Average postoperative distraction was 5.8 mm, and angular reduction was 8.5 ° on the CV and 9.8 ° on ART. At follow-up, the loss of correction was respectively 3.2 ° and 6.1 ° on CV and ART. The secondary compaction was 2.5 mm. Secondary regional kyphosis was higher in short instrumentation (7 ° against 5.2 °) as well as for patients with a BMI ≥ 25.